Global trends of research on depression in breast cancer: A bibliometric study based on VOSviewer - Chen, Ling; Ren, Tingting; Tan, Yun; Li, Hong (Frontiers in Psychology, 2022)
Background Depression is common psychiatric morbidity in breast cancer survivors, seriously affecting patients’ quality of life and mental health. A growing body of research has investigated depression in breast cancer. However, no visual bibliometric analysis was conducted in this field. This study aimed to visualize the literature to identify hotspots and frontiers in research on breast cancer and depression. Methods The publications related to depression in breast cancer were retrieved in the Web of Science Core Collection between 1 January 2002 and 17 March 2022. VOSviewer was used to identify co-occurrences and collaborations among countries, institutions, and keywords. CiteSpace was used to detect keyword bursts. Results A total of 7,350 articles and reviews related to depression in breast cancer were identified. From 2002 to 2022, the United States and the People’s Republic of China were the most productive countries in this field. The University of California, Los Angeles, and the University of Toronto were the most productive institutions in this field. The Journal of Psycho-oncology, followed by Supportive Care in Cancer and the Journal of Clinical Oncology, had the most publications on depression in breast cancer. Of the top 10 journals, seven were from the United States, two were from England, and one was from Germany. Five research hotspots of depression in breast cancer were identified by co-word analysis. Research on post-traumatic growth, spiritual interventions, cognitive-behavioral therapy, physical activity, and symptom cluster management of depression in breast cancer was relatively mature in the core hotspots. Burst detection of keywords on depression in breast cancer showed the latest hotspots, such as mental health, cancer survivor mortality, and activity. Conclusion The research on depression in breast cancer is growing. Attention should be paid to the latest hotspots, such as mental health, cancer survivor, mortality, exercise, and physical activity.